The Lepidoptera of White Sands National Monument, Otero County, New Mexico, USA 10. A remarkable new white species of Chionodes Hübner (Gelechiidae) - Metzler, Eric H.; Landry, Jean-François (Zootaxa, 2016)
The U.S. National Park Service initiated a 10-year study, in late 2006, of the Lepidoptera at White Sands National Monument, Otero County, New Mexico. Chionodes bustosorum sp. n., described here, was discovered in 2010, during the third year of the study. The male imago and male genitalia are illustrated, and its DNA barcode is compared to that of seven other species of Chionodes from western North America.